Preparation, characterization, and lead removal appraisal of zinc aluminate prepared at different calcination temperatures. Issue 10 (23rd May 2018) - Abdullah, Faizuan; Mohd Yusoff, Abdull Rahim; Wan Abu Bakar, Wan Azelee; Ismail, Razali; Syafiuddin, Achmad
Abstract : We propose a procedure to remove lead (Pb) via catalytic chelation using peracetic acid (PAA) catalyzed using zinc aluminate (ZnAl2 O4 ) prepared at different calcination temperatures of 900, 1, 000, and 1, 100 °C. In addition, their characterization in terms of the thermogravimetry analysis‐differential thermal analysis (TGA‐DTA), X‐ray diffraction (XRD), field‐emission scanning electron microscopy‐energy dispersive X‐ray analysis (FESEM‐EDX), Brunauer–Emmett–Teller (BET) analysis, Fourier transform infrared spectroscopy (FTIR), inductively coupled plasma mass spectrometry (ICP‐MS), and X‐ray photoelectron spectroscopy (XPS) was achieved. Moreover, response surface methodology (RSM) was employed for modeling. This study confirms that the properties of ZnAl2 O4 are highly influenced by the calcination temperature. In addition, up to 95.3% of Pb can be removed using the proposed approach by employing optimum parameters such as temperature, pH, treatment time, PAA concentration, catalyst loading, and dissolved oxygen. Abstract : We propose a procedure to remove lead (Pb) via catalytic chelation using peracetic acid (PAA) catalyzed by zinc aluminate (ZnAl2 O4 ) prepared at different calcination temperatures. Up to 95.3% of Pb can be removed by employing optimum parameters such as temperature, pH, treatment time, PAA concentration, catalyst loading, and dissolved oxygen.